PENERAPAN STRATEGI ACTIVE KNOWLEDGE SHARING UNTUK MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS XA SMA PIRI 1 YOGYAKARTA - Rina Apriliana; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
The Implementation of Active Knowledge Sharing Strategies to Increase Students' Interest and Achievement Math High School of Tenth grade students of SMA PIRI 1 Yogyakarta in Academic Year 2013/1014. This research is Classroom Action Research (CAR) conducted collaboratively. The subjects in this study are The tenth grade students of SMA PIRI 1 Yogyakarta, amounting to 26 students. While the object is interested in mathematics learning and achievement gained from the application of Active Knowledge Sharing learning. The results showed that the interest and the achievement of learning math by using the Active Learning Strategies of Knowledge Sharing have increased. This is indicated by an increase in the average yield percentage interest in learning math sheet observation on Pre cycle 1 increased by 51.92% 62.18% in the first cycle and 78.21% in the second cycle. Interest in learning mathematics questionnaire sheet for each cycle, ie at pre cycle student interest at 63.28% increased to 72.47% in the first cycle, and increased in the second cycle becomes 84.37%. In addition, the average value of student achievement has increased the percentage pre cycle completeness of 55.15 with 23.08% (6 students) increased to 64.20 with the percentage of completeness 50.00% (13 students) in the first cycle, while the second cycle increased to 79.41 with the percentage of completeness 76.92% (20 students). Given the Active Knowledge Sharing strategy could increase interest and achievement of learning mathematics teachers should implement these strategies in teaching learning.